2018
DOI: 10.1111/sms.13023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different endurance exercise modalities on migraine days and cerebrovascular health in episodic migraineurs: A randomized controlled trial

Abstract: Aerobic exercise training is a promising complementary treatment option in migraine and can reduce migraine days and improve retinal microvascular function. Our aim was to elucidate whether different aerobic exercise programs at high vs moderate intensities distinctly affect migraine days as primary outcome and retinal vessel parameters as a secondary. In this randomized controlled trial, migraine days were recorded by a validated migraine diary in 45 migraineurs of which 36 (female: 28; age: 36 (SD:10)/BMI: 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(115 citation statements)
references
References 44 publications
3
105
0
7
Order By: Relevance
“…All studies included patients with migraine classified by the ICHD-II as mentioned in the inclusion criteria. In three studies, patients were excluded if they performed any kind of regular aerobic training before the start of the study [25] or at least 12 weeks prior to the study [26, 28]. The number of patients enrolled in the different studies ranged from 16 to 110 with a total number of 357 patients with migraine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies included patients with migraine classified by the ICHD-II as mentioned in the inclusion criteria. In three studies, patients were excluded if they performed any kind of regular aerobic training before the start of the study [25] or at least 12 weeks prior to the study [26, 28]. The number of patients enrolled in the different studies ranged from 16 to 110 with a total number of 357 patients with migraine.…”
Section: Resultsmentioning
confidence: 99%
“…Several types of aerobic exercise were used in the studies. One study used a walking program [27], one a combination of cross-training, walking, jogging and cycling [29], two a jogging protocol [25, 26], one a behavioral weight loss program [24] and finally cycling was used in one study [28]. The walking program [27] consisted of 40–45 min of fast walking and was controlled by heartrate and Borg-scale or Rate of Perceived Exertion scale (RPE) [31].…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the benefits of exercise on post‐concussive symptom resolution, outlined in detail above, a recent systemic review and meta‐analysis have shown that exercise can reduce the frequency, duration, and severity of migraine headaches 125‐128 . Additionally, exercise has been shown to be either additive (amitriptyline) or non‐inferior (topiramate) to pharmaceuticals in the management of migraine .…”
Section: Return To Learn and Return To Play (Rtl/rtp) Post‐mtbimentioning
confidence: 99%
“…Using a 3‐armed RCT, Hanssen et al 46,47 examined the differential effects of aerobic activities on multiple health outcomes among episodic migraineurs. Compared to moderate continuous aerobic training, high intensity interval training had a more pronounced effect on reducing migraine days and cerebrovascular outcomes, but overall, aerobic activity exerted positive effects for migraineurs 46,47 . In light of the greater conferred benefit of higher intensity physical activity, the authors concluded that the positive effects of exercise may be dependent on both type of exercise and its intensity 46 .…”
Section: Discussionmentioning
confidence: 99%